한·GCC FTA 협상대비 농업분야 영향분석 및 대응방안 연구 - 임송수 (한국농촌경제연구원, 2008)
This study has performed economic impact analysis for upcoming Korea-GCC FTA in the agricultural sector and proposed some negotiation strategies. Research outcomes are summarized as follows. First, agricultural trade is likely to be of little interest between the two partners considering present states of agricultural structure and trade balance. Second, it suggests that Korea follow a minimalist approach to making market access commitments given the nature of agricultural sensitivity within the country and relatively weak potential gains expected from both sides. Third, since increases in market access will be mostly beneficial to processed and preferential food or products, attention should be warranted in these areas during negotiations. Fourth, the rule of origin must take into account the fact that Korea exports a number of value added food using imported ingredients. Besides, it needs to focus attention on prevailing re-export practices by the GCC countries. Finally, securing safeguard is important only when the resulting compensation is not beyond the reach of the government.